ANALISIS KINERJA PERANGKAT KECAMATAN DALAM PELAYANAN PUBLIK (Studi Kasus Kantor Camat Tanah Putih Kabupaten Rokan Hilir) - ", Hendri; ", Ernawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Performance analysis for Public Service. Measurements in a performance that is very necessary with a view to identify and improve the effectiveness of performance on a system. In this research, performance analysis and performance measurement focused on the sub-districts in the district of Tanah Putih in providing services. in this case because according to the information extracting and growing issue that is problematic dikecamatan public services such convoluted, complicated, confusing and do not have a clear time accuracy. While the principles of the ideal of public service does not comply with the conditions of service are held. Departing from the researchers were interested in examining these issues and attempt to provide solutions for improving public services in the district of Tanah Putih Rokan Hilir regency of Riau province.The purpose of this study to investigate the performance of the device districts in providing public services, in addition to knowing the factors that hinder the performance of the districts in providing public services in the Tanah Putih district of Rokan Hilir. The results showed that the performance of the device has not been effective Tanah Putih districts and the factors that hinder them not maketh Standard Operating Procedures and guidelines in carrying out the performance of labor services is not yet fully understands its obligations and duties and principles of public service ideal.Kata Kunci : Performance analysis, Public Service, productifity, service quality, responcivity, akuntability.